Analysis of Strategies To Reduce Medication Errors In Hospitals: A Literature Review - Admaja, Septian Yuda; Rosa DM., Rizka (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Medication errors are a critical issue in healthcare and can have a serious impact on patients. Hospitals as health care centers have a great responsibility in maintaining patient safety. The importance of reducing medication errors in hospitals is the basis for the urgency of this study. The purpose of this study is to analyze various strategies that can be implemented in reducing medication errors in hospitals. This research was conducted through a literature review method. Data was collected through searching various articles, journals, and scientific publications related to strategies to reduce medication errors in hospitals. The data collected from the literature study were analyzed comprehensively. The results showed that strategies to reduce medication errors in hospitals include electronic prescription, correct patient principle, monitoring, unit-dose dispensing system (UDD), read-back guidance using checklists, Electronic Medication Management (EMM) system, careful prescription writing, patient safety programs, measuring the level of knowledge, attitudes and behaviors of nurses about medical errors and prevention at each stage of the medication use process